MN1 Neurodevelopmental Disease-Atypical Phenotype Due to a Novel Frameshift Variant in the MN1 Gene - Tian, Qi; Shu, Li; Zhang, Pu; Zeng, Ting; Cao, Yang; Xi, Hui; Peng, Ying; Wang, Yaqin; Mao, Xiao; Wang, Hua (Frontiers in Molecular Neuroscience, 2021)
Background:MN1 C-terminal truncation (MCTT) syndrome is caused by variants in the C-terminal region of MN1, which were first described in 2020. The clinical features of MCTT syndrome includes severe neurodevelopmental and brain abnormalities. We reported on a patient who carried the MN1 variant in the C-terminal region with mild developmental delay and normal brain magnetic resonance image (MRI). Methods: Detailed clinical information was collected in the pedigree. Whole-exome sequencing (WES) accompanied with Sanger sequencing validation were performed. A functional study based on HEK239T cells was performed. Results: A de novo heterozygous c.3734delT: p.L1245fs variant was detected. HEK239T cells transinfected with the de novo variant showed decreased proliferation, enhanced apoptotic rate, and MN1 nuclear aggregation. Conclusion: Our study expended the clinical and genetic spectrum of MCTT which contributes to the genetic counseling of the MN1 gene.